Assessment of environmental sustainability of nickel required for mobility transition - Golroudbary, Saeed Rahimpour; Kraslawski, Andrzej; Wilson, Benjamin P.; Lundström, Mari (Frontiers in Chemical Engineering, 2023)
The increasing use of nickel in battery technologies has resulted in the continuous growth of demand for nickel over recent years. Nickel was added to the list of critical materials by the United States Geological Survey (USGS) already in 2021. Nickel (Ni) in batteries (e.g., nickel-metal hydride battery (NiMH), lithium nickel cobalt aluminum oxide (NCA) and lithium nickel manganese cobalt oxide (NMC)) aim to ensure higher energy density and greater storage capacity. Two of the most commonly used batteries, NCA and NMC, contain 80% and 33% of nickel, respectively. Demand for recycled nickel is growing, however, a systematic analysis of the sustainability of its recycling is still missing. Therefore, we provide a comprehensive assessment of the sustainability of the global primary and secondary production of nickel. Using system dynamics modelling integrated with geometallurgy principles and by analyzing the processing routes (pyrometallurgical and hydrometallurgical processes), we quantify the key environmental concerns across the life cycle of primary and secondary nickel required for sustainable mobility transition. Energy consumption, water use, and related emissions are assessed for all stages of the nickel supply chain, from mining to recycling. Our analysis shows the possibility of reducing the emissions by around 4.7 mt for GHG, 6.9 kt for PM2.5, 34.3 t for BC, 2.8 kt for CH4, 7.5 kt for CO, 3.3 mt for CO2, 169.9 t for N2O, 3.8 kt for NOx, 11.8 kt for PM10, 104.8 t for POC, 1.6 mt for SOx, and 232.5 t for VOC by engaging in the secondary production of nickel through the recycling of batteries. However, identical growth rate of energy consumption and water use compared to nickel mass flows means no technical progress has been achieved in different stages of the nickel supply chain towards sustainability over the period 2010-2030. Therefore, an improvement in technology is needed to save energy and water in nickel production processes. The results and findings of this study contribute to a better understanding of the necessity for improving closed-loop supply chain policies for nickel.